Capacitor Lifetime Extension in a Hybrid Active Neutral-Point-Clamped Inverter with Reduction of DC-Link Ripple Current and Common-Mode Voltage - An, Sang Won; Kim, Seok Min; Lee, Kyo Beum (IEEE Access, 2021)
This paper proposes a reduction method for DC-link ripple current and common-mode voltage (CMV) in a hybrid active neutral-point-clamped (ANPC) inverter. A Si and SiC hybrid ANPC inverter has been developed recently to overcome the extremely high cost of a full-SiC ANPC inverter. A hybrid ANPC requires much fewer SiC MOSFETs than a full-SiC ANPC inverter while providing a comparable power density. Voltage source inverters such as hybrid ANPC inverters utilize electrolytic capacitors, which have a large capacitance per volume, as a DC link. However, an electrolytic capacitor is one of the most vulnerable components in a power electronic converter due to its small allowable ripple current. A large ripple current flowing into the electrolytic capacitor generates a heat loss, which shortens the lifetime of the capacitor. Furthermore, the common-mode voltage (CMV) causes an undesirable leakage current and electromagnetic interference. The CMV depends on the pulse-width modulation of the voltage source inverters. The proposed method enhances the reliability of the hybrid ANPC inverter by reducing the DC-link ripple current and CMV simultaneously. The effectiveness and validity of the proposed method are verified through simulations and experimental results.
Keywords: Active neutral point clamped; Common mode voltage; Lifetime extension; Power densities; Power electronic converters; Reduction method; Ripple currents; Voltage source inverter; Capacitor; common-mode voltage; hybrid ANPC inverter; neutral point ripple current; space vector modulation